APPROACHES TO BUILDING COMPETENCE OF INTERCULTURAL INTERCOURSE OF FUTURE SPECIALISTS IN JAPANESE STUDIES - A. V. Derkach (Vestnik MGIMO-Universiteta, 2013)
The article presents the results of the psycho-pedogogical research in the field of technology of professional training of Japanese language specialists. The author analyses the theoretical approaches of the modern knowledge in the humanities to defining the concept of “intercourse” and analyses its correlation with the term “communication”. The author comes to the conclusion that it is important to work out a modern technology which would help to imorove the efficiency of building the competence of intercultural intercourse of future specialists. The technology is to include three interconnected stages of training students in an artificial, synthetic and authentic linguistic environment. The suggested technology of stage-based training of Japanese language specialists has a big potential and can be effectively used in the open educational environment of modern Russia. The author further argues that if we look at the process of intercourse through the prism of modern integration processes, we will see that the modern system of education in Russia needs more sophisticated educational technologies aimed at preparing university graduates for full-scale cross-cultural communication with representatives of various languages and cultures.